HIRAID: An evidence-informed emergency nursing assessment framework. Issue 2 (May 2015) - Munroe, Belinda; Curtis, Kate; Murphy, Margaret; Strachan, Luke; Buckley, Thomas
Summary Introduction Emergency nurses must be highly skilled at performing accurate and comprehensive patient assessments. In 2008, the inaugural emergency nursing assessment framework (ENAF) was devised at Sydney Nursing School, to provide emergency nurses with a systematic approach to initial patient assessment. In 2014 the assessment framework was re-developed to reflect the most recent evidence. Aim To describe the process and evidence used to re-develop ENAF, to provide ED nurses with an evidence-informed approach to the comprehensive assessment of patients presenting to ED after triage, so that it may be implemented and tested in the clinical (simulated) setting. Methods A thorough literature review was conducted to inform the re-development of ENAF. Literature review findings were reviewed and ENAF was re-developed by a panel of expert emergency nursing clinicians using the Delphi Technique. Results Modifications to ENAF were undertaken and a new, more comprehensive assessment framework was developed titled 'HIRAID'. HIRAID is informed by current evidence, comprising of seven assessment components: History; Identify Red flags; Assessment; Interventions; Diagnostics; reassessment and communication. Conclusion HIRAID provides an evidence-informed systematic approach to initial patient assessment performed by emergency nurses after triage. Evaluation is now needed to determine its impact on clinician performance and patient safety.